(untitled) (Journal of Patan Academy of Health Sciences, 2016)
Introductions: The pattern of ocular malignant tumors in institutes of Eastern Nepal was analyzed by a retrospective study. Ocular malignant tumors are relatively rare compared to other eye lesions, and require immediate diagnosis and management. Ignorance or unawareness can result into debility, loss of vision, and even death. This study provides spectrum of ocular malignant tumor correlating its pathological and clinical findings. Methods: This cross sectional study includes ninety-six cases of ocular malignant tumors diagnosed in the department of pathology from January 2005 to December 2009. Relevant history, clinical findings and light microscopic findings were reviewed. Descriptive analysis was done. Results: A total of 96 patient’s records were studied. Age ranged between 1-90 years. Male to female ratio was 1.4:1. Retinoblastoma was found in 34.5%, basal cell carcinoma in (18%), squamous cell carcinoma in 14.5% and malignant melanoma in 10.5%. Conclusions: Early diagnosis and management help to reduce debility and loss of vision in the patients as well as help ophthalmologist in shaping the strategy for diagnosis and management of malignant neoplasm. This help in decreasing morbidity and mortality of the patient. Journal of Patan Academy of Health Sciences, Vol. 3, No. 1, 2016. page: 15-17